Seeds of yesterday [videorecording (DVD)] - Lewis, Jason, 1971-; Hanratty, Sammi, 1995-; Konechny, Anthony; Andrews, V. C. (Virginia C.)
The Dollangangers continue to coexist miserably, as their deeply troubled relationships, dark secrets, and tragedies come to a head in a way that will haunt the family and its progeny forever.